2018
DOI: 10.1044/2018_lshss-17-0098
|View full text |Cite
|
Sign up to set email alerts
|

Math Difficulties and Working Memory Growth in English Language Learner Children: Does Bilingual Proficiency Play a Significant Role?

Abstract: Growth in the executive component of WM is significantly related to growth in math computation, and increased bilingual proficiency across testing waves yielded positive gains in both math and cognitive performance in children with MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…These studies have found that the degree of bilingual language exposure can result in incremental cognitive benefits in children and older adults (Poarch & Van Hell, 2012). Additionally, gains in EF (i.e., working memory) and high language proficiencies across both languages in bilingual NT children predicted gains in math skills, even among bilingual children with significant math difficulties (Blair & Razza, 2007; Bull, Espy, & Wiebe, 2008; Swanson, Kong, & Petcu, 2018). These findings suggest a complex relationship between bilingual language learning, EF, and academic development in NT children.…”
Section: Academic Skills In Nt Bilingual Childrenmentioning
confidence: 98%
“…These studies have found that the degree of bilingual language exposure can result in incremental cognitive benefits in children and older adults (Poarch & Van Hell, 2012). Additionally, gains in EF (i.e., working memory) and high language proficiencies across both languages in bilingual NT children predicted gains in math skills, even among bilingual children with significant math difficulties (Blair & Razza, 2007; Bull, Espy, & Wiebe, 2008; Swanson, Kong, & Petcu, 2018). These findings suggest a complex relationship between bilingual language learning, EF, and academic development in NT children.…”
Section: Academic Skills In Nt Bilingual Childrenmentioning
confidence: 98%
“…Mathematics difficulties among children with language disorders can be partially explained by their working memory abilities (Cross, Joanisse, & Archibald, 2019; Fyfe, Matz, Hunt, & Alibali, 2019). Furthermore, the relation between mathematics development and working memory growth is influenced by language proficiency, especially among second-language learners who perform mathematics in their second language (Swanson, Kong, & Petcu, 2018). Taken together, these findings further suggest that working memory may be a key factor in explaining the relation between language and mathematics.…”
Section: The Language Function Hypothesis In Mathematicsmentioning
confidence: 99%
“…When applied to EL children, Swanson et al (2004) found significant cross-language transfer in Grade 1 children on L1 STM and WM measures and L2 English word identification. Additional studies found that growth on measures of Spanish vocabulary, reading, STM, and WM accounted for significant variance in (a) predicting growth in English reading (e.g., Swanson et al, 2006) and (b) growth on Spanish measures of naming speed, STM, and working memory predicted L2 math performance (e.g., Swanson et al, 2019b).…”
Section: Do Specific Cognitive Measures Predict Latent Class Membership?mentioning
confidence: 99%
“…For example, deficits in the phonological system (phonological storage) have been attributed to RD in English (e.g., Stanovich & Siegel, 1994) and Spanish (e.g., González & Valle, 2000). More recent studies have suggested that executive processes related to WM, are also significantly related to L2 reading, as well as and math performance (e.g., Swanson et al, 2015Swanson et al, , 2019aSwanson et al, , 2019b). This executive system reflects controlled attention because the information to be recalled is presented in the context of competing information.…”
Section: Do Specific Cognitive Measures Predict Latent Class Membership?mentioning
confidence: 99%